First report of Coolia palmyrensis in Korea: seasonal and spatial distribution of C. palmyrensis and C. malayensis in Korean coastal waters - Hyung, Jun-Ho; Moon, Seung Joo; Lee, Hangy; Park, Jaeyeon (Frontiers in Marine Science, 2024)
Distribution patterns of benthic dinoflagellates that are widely observed in tropical and temperate waters and have toxic potential are changing in response to ocean climate change. Although there have been no outbreaks associated with the genus Coolia affecting humans, it is crucial to understand their changing distribution and clearly identify the species in the study area to prepare for potential toxic events. In this study, five strains of Coolia species were isolated from macroalgae samples collected from Jeju Island and the eastern coastal waters of Korea. Through morphological and molecular analysis of these isolates, one strain was identified as Coolia palmyrensis, marking the first report of this species in Korea, and four strains as C. malayensis. One of the C. malayensis strains was isolated in Pohang on the eastern coast of Korea, where it had not been previously reported. From 2021 to 2023, monitoring of Jeju Island using a quantitative polymerase chain reaction (PCR) assay revealed that C. palmyrensis cells occurred mostly in autumn, with a maximum density of 242 cells g-1, and overwintering populations were observed in 2023. However, C. malayensis cells were not observed in this area. Additionally, C. malayensis was observed in Pohang and Ulsan, located further north than Jeju Island with maximum cell densities of 537 and 201 cells g-1, respectively. These data and our decade of monitoring experience confirmed the introduction and establishment of C. palmyrensis and habitat shift of C. malayensis in Korean coastal waters. This study provides advances for understanding of the relationships between climate-driven alterations and biogeographic distribution of these species.